1981
DOI: 10.1172/jci110146
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Effects of Arginine Vasopressin during Fluid Deprivation in the Rat

Abstract: A B S T R A C T The vascular effects of arginine vasopressin (AVP) were examined in conscious SpragueDawley rats. In six control rats, synthetic AVP at a dose of40 ng/kg, injected as an intravenous bolus, resulted in a rise in mean arterial blood pressure (BP) from 127 to 149 mm Hg (P < 0.005). No tachyphylaxis was observed after a second AVP bolus administered 30 min later, as BP increased from 125 to 150 mm Hg, P < 0.005. In a second group of six rats, 1-deamino penicillamine, 2-(O-methyl) tyrosine AVP ([dPT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
45
1

Year Published

1983
1983
1994
1994

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(48 citation statements)
references
References 11 publications
2
45
1
Order By: Relevance
“…Previous studies have shown that the effects of d(CH 2 )Tyr(Me)AVP did not involve norepinephrine or Ang II changes. 20 Therefore, our data suggest that in conscious dogs L-NAME may cause a release of AVP. Inhibition of V, receptors thus would attenuate the MAP response.…”
Section: Discussionmentioning
confidence: 61%
“…Previous studies have shown that the effects of d(CH 2 )Tyr(Me)AVP did not involve norepinephrine or Ang II changes. 20 Therefore, our data suggest that in conscious dogs L-NAME may cause a release of AVP. Inhibition of V, receptors thus would attenuate the MAP response.…”
Section: Discussionmentioning
confidence: 61%
“…24 It should also be noted that the MAP measured by this method is significantly lower than the MAP recorded in studies using other direct measurements in restrained animals. 15 28 the plasma renin activity of Brattleboro rats was found to be significantly higher than in agematched Long-Evans rats. The difference may either represent a compensatory mechanism counter-balancing the absence of the pressor action of vasopressin or it may be a consequence of the volume contraction of Brattleboro rats.…”
Section: Discussionmentioning
confidence: 76%
“…42 This dose completely prevented the pressor response to 10 mM of exogenous vasopressin in every animal studied. The animals were then infused with CaCl 2 (n = 7) or NaCl (n = 5), and MAP was measured, as described before.…”
Section: Role Of Vasoconstrictive Hormones On the Pressor Response Tomentioning
confidence: 86%